2015
DOI: 10.1093/molbev/msv196
|View full text |Cite
|
Sign up to set email alerts
|

Widespread and Adaptive Alterations in Genome-Wide Gene Expression Associated with Ecological Divergence of TwoOryzaSpecies

Abstract: Ecological speciation is a common mechanism by which new species arise. Despite great efforts, the role of gene expression in ecological divergence and speciation is poorly understood. Here, we conducted a genome-wide gene expression investigation of two Oryza species that are evolutionarily young and distinct in ecology and morphology. Using digital gene expression technology and the paired-end RNA sequencing method, we obtained 21,415 expressed genes across three reproduction-related tissues. Of them, approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(70 citation statements)
references
References 99 publications
8
60
0
Order By: Relevance
“…Meanwhile, Illumina-based plastid sequencing has been proven to be a valid and cost-effective way to acquire the complete cp DNA. Many assembled cp DNA of non-model species also have been obtained and employed for the study of differential gene expression, genetic markers development [28], phylogenomics analysis [29], as well as for detecting selection and inferring adaptive evolution within and among angiosperm species [30,31]. …”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Illumina-based plastid sequencing has been proven to be a valid and cost-effective way to acquire the complete cp DNA. Many assembled cp DNA of non-model species also have been obtained and employed for the study of differential gene expression, genetic markers development [28], phylogenomics analysis [29], as well as for detecting selection and inferring adaptive evolution within and among angiosperm species [30,31]. …”
Section: Introductionmentioning
confidence: 99%
“…In these evolutionary contexts, ecological niche modelling (ENM) has been widely used to identify the environmental niche divergence between closely related taxa (Kozak et al 2008;Loera et al 2012;Guo et al 2015;Qu et al 2015). By integrating molecular phylogeography data, ENM has been conducted to detect whether pairs of sister species are more ecologically divergent than random expectation and even to clarify the relationship between genetic differentiation and abiotic factors (Knouft et al 2006;Blair et al 2013;Zhang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, little is known on the effect of stress as a selective agent on gene regulation. A report on rice demonstrated that regulatory divergence is associated with ecological speciation and adaptive alterations (Guo et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(O. rufipogon and O. nivara;Guo et al 2015) and among species of Arabidopsis (A. lyrata,A. halleri and A. thaliana;He et al 2016).…”
mentioning
confidence: 99%